PENGARUH KAPASITAS KELEMBAGAAN, KOORDINASI, DAN PENGAWASAN TERHADAP AKUNTABILITAS KINERJA PEMERINTAH KOTA BOGOR PROVINSI JAWA BARAT - Syahrir Syahrir (Jurnal Kebijakan Pemerintahan, 2019)
The Influence of Institutional Capacity, Coordination and Supervision of the Accountability of the Performance of the Government of Bogor City, West Java Province. The phenomenon used as the object of research is the accountability of the performance of the Bogor City government. The purpose of the study was to discuss the effect of institutional capacity, coordination, and supervision on the accountability of the performance of the Bogor City Government. Research uses a quantitative research approach. The study sample of 383 employees was taken from the study population of 8944 employees using the Slovin formula. Data collection techniques used library research, questionnaire techniques and observation. Data analysis used multiple regression analysis/ multiple regression. The results of the study are as follows. There is an influence of institutional capacity on the accountability of the performance of the Bogor City government. There is an influence of coordination on the accountability of the performance of the Bogor City government. There is an influence of supervision on the accountability of the performance of the Bogor City government. There is an influence of institutional capacity, coordination, and joint supervision of the accountability of the performance of the Bogor City government. From the measurement of multiple regression it is known that the contribution of institutional capacity is greater than the contribution of coordination and the contribution of supervision to the accountability of the performance of the Bogor City government. Keywords: institutional capacity, coordination, supervision, performance accountability